College Chemistry, 1. - Indira, L. (Himalaya Pub. House, 2010)
The aim of this book has been to provide; The subject-matter is a clear and simple style with figure and illustrations. A number of solved problems for a better understanding of the theoretical aspects of the subject. Elaborate discussion of IUPAC nomenclature of organic compounds. Detailed discussion of electronic effects and reaction mechanisms of various reactions confirming to the syllabus. A large number of questions at the end of each chapter to motivate the students.